Digital Fatigue in the Teaching Profession: The Role of Workload and Technostress on Teacher Performance through Work-Family Conflict and Burnout - Indra Dwi Sukmawati; Rahmat Agus Santoso; Abdul Kholid Achmad (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study aims to analyze the phenomenon of digital fatigue in the teaching profession by examining the influence of workload and technostress on teacher performance through work-family conflict and burnout as mediating variables.   Design/methodology/approach – This study employed a quantitative approach with an explanatory research design. The population consisted of 38 senior high school and vocational high school teachers in Kebomas District, Gresik. Because the population was relatively small, saturated sampling was applied, involving all teachers as respondents. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). Finding/Results – The results revealed that workload had a significant negative effect on teacher performance (β = -0.231; p = 0.005), while technostress also had a significant negative effect on teacher performance (β = -0.267; p = 0.002). Furthermore, workload significantly increased work-family conflict (β = 0.421; p < 0.001), and technostress also significantly increased work-family conflict (β = 0.398; p < 0.001). Work-family conflict had a significant positive effect on burnout (β = 0.512; p < 0.001), whereas burnout had a significant negative effect on teacher performance (β = -0.478; p < 0.001). Mediation analysis indicated that work-family conflict and burnout acted as significant mediators. Originality/Value – This study contributes to the literature by developing and empirically testing an integrated model that explains how digital work demands affect teacher performance through sequential psychological processes involving work-family conflict and burnout. The findings extend the Job Demands–Resources (JD-R) Theory by demonstrating the interconnected roles of work-family conflict and burnout as serial mediators.